2006
DOI: 10.1890/0012-9658(2006)87[3095:lmdaht]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Linking Movement, Diving, and Habitat to Foraging Success in a Large Marine Predator

Abstract: Establishing where and when predators forage is essential to understanding trophic interactions, yet foraging behavior remains poorly understood in large marine carnivores. We investigated the factors leading to foraging success in gray seals (Halichoerus grypus) in the Northwest Atlantic in the first study to use simultaneous deployments of satellite transmitters, time depth recorders, and stomach-temperature loggers on a free-ranging marine mammal. Thirty-two seals were each fitted with the three types of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
132
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(138 citation statements)
references
References 85 publications
6
132
0
Order By: Relevance
“…Detailed records of prey abundance and distribution and accurate indices of feeding are difficult to obtain for the majority of species and although visual assessment of prey capture is possible for some species (Seminoff et al, 2006;Elliott et al, 2008), in most cases, indirect parameters have been used as a proxy (e.g., gastric or visceral temperature changes, mouth/beak opening or head/jaw movement, accelerometer signatures; Sepulveda et al, 2004;Gleiss et al, 2011aGleiss et al, , 2013Nakamura et al, 2011Nakamura et al, , 2015Carroll et al, 2014;Nakamura and Sato, 2014). For efficient foraging by predators, patterns of habitat use are assumed to reflect the distribution, density and quality of prey resources (Stephens and Krebs, 1986;Austin et al, 2006;Carroll et al, 2017). Therefore, horizontal and vertical movements of marine predators in addition to the frequency of dives, their persistence and other characteristics are expected to be related to distinct activities such as foraging or traveling (e.g., Horodysky et al, 2007;Thomson et al, 2011;Dragon et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed records of prey abundance and distribution and accurate indices of feeding are difficult to obtain for the majority of species and although visual assessment of prey capture is possible for some species (Seminoff et al, 2006;Elliott et al, 2008), in most cases, indirect parameters have been used as a proxy (e.g., gastric or visceral temperature changes, mouth/beak opening or head/jaw movement, accelerometer signatures; Sepulveda et al, 2004;Gleiss et al, 2011aGleiss et al, , 2013Nakamura et al, 2011Nakamura et al, , 2015Carroll et al, 2014;Nakamura and Sato, 2014). For efficient foraging by predators, patterns of habitat use are assumed to reflect the distribution, density and quality of prey resources (Stephens and Krebs, 1986;Austin et al, 2006;Carroll et al, 2017). Therefore, horizontal and vertical movements of marine predators in addition to the frequency of dives, their persistence and other characteristics are expected to be related to distinct activities such as foraging or traveling (e.g., Horodysky et al, 2007;Thomson et al, 2011;Dragon et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, observations at emperor penguin colonies have shown that foraging trips vary in duration as the breeding season goes on (Kirkwood and Robertson 1997a), with the suggestion being that this is brought about by changes in the environment. The complexity of environmental conditions, both biotic and abiotic, with which emperor penguins have to contend ultimately distil out into two major behavioural patterns which are expressed during foraging: (1) travelling behaviour, where birds move quickly and directly through regions inappropriate for foraging, and (2) searching behaviour, where a reduced rate of overall travel results from greater track tortuosity in regions where prey is most likely to be located (Wilson 1995;Leopold et al 1996;Jaquet and Whitehead 1999;Nolet and Mooij 2002;Wilson 2002;Markman et al 2004;Austin et al 2006). The time allocated to each of these two behaviours results in a total foraging trip duration, which modulates the rate at which chicks can acquire food and thus grow appropriately.…”
Section: Introductionmentioning
confidence: 99%
“…These included shallow, repeated dives with short surface-time intervals, as well as deeper, repeated U-shaped dives with comparatively longer surface recovery times. Such dive types have been attributed to foraging behaviors in an array of top marine predators such as gray seals (Halichoerus grypus; Austin et al 2006), southern elephant seals (Gallon et al 2013), Australian fur seals (Arctocephalus pussillus; Arnould and Hindell 2001), harbor seals (Phoca vitulina; Baechler et al 2002), and others. Parameters corresponding to aperiodic solutions of the AR(2) process, or a correlated vertical random walk, were termed exploratory diving.…”
Section: Discussionmentioning
confidence: 99%
“…Marine animal movement is a complex 3-D process that does not always simplify into lower dimensions, and there is mounting evidence to demonstrate the potential perils of inferring animal behavior based on horizontal trajectories alone (e.g., McClintock et al 2013 and references therein). For instance, horizontal straightness indices (i.e., area restricted searches) poorly correlate with feeding behaviors (Austin et al 2006, Weimerskirch et al 2007. First passage time is a movement metric that measures animal passage through a horizontal region of fixed radius and has been linked to environmental variables, but it can be confounded by the slow speeds of resting behaviors, and the fast speeds of foraging behavior along tortuous paths; both behaviors lead to similar times to traverse a fixed radius region.…”
Section: Introductionmentioning
confidence: 99%